Sierra Leone Flooding 2024: An Urgent Call For Sustainable Flood Risk Management - Salieu Sankoh Alimamy (Universitas Airlangga, 2026)
Flooding remains one of Sierra Leone’s most severe natural hazards, with the 2024 flood event displacing thousands, destroying infrastructure, and worsening food and health insecurity. Despite efforts by the National Disaster Management Agency (NDMA), inadequate preparedness, poor urban planning, and climate-induced extreme weather continue to hinder flood management. This study assesses the effectiveness of current flood risk management policies, focusing on the role of the NDMA during the 2024 floods. Key gaps in preparedness, response, and resilience are identified. The study highlights the link between displacement and climate vulnerability and proposes community-based, adaptive strategies. Recommendations are provided to enhance flood resilience, improve response coordination, and strengthen recovery frameworks. These findings aim to support policymakers and disaster practitioners in building a more sustainable flood risk management system in Sierra Leone.